Immune relationahip between Pseudomonas aeruginosa and Listeria monocytogenes - Alwan, Mohammed Jawed; yassin zagir , Khalid; mohammed Al-Jebouri, Nagham (The Iraqi Journal of Veterinary Medicine, 2009)
In order to known the effect of whole sonicated L. monocytogenes antigen on as mice experimentallyinfected with P.aeruginosa.,30 white mice,8-12 weeks age, were divided randomly into three equalgroups..The 1st group was immunized subcutaneously twice with (0.5)ml of whole sonicated P.aeruginosaantigen(7.6mg/ml concentration protein) ,with two weeks intervals.The cellular immune responses waschecked at (27) days post-immunization The animals of the 1st and 2nd groups were challengedsubcutaneously with (0.5) ml of bacterial suspension contain1X10 9cfu/ml of virulent P.aeruginosa whilethe 3rd group was inoculated S/C with (0.5)ml of sterile phosphate buffer saline and served as controlnegative group.. The resuls showed that the prepared antigen antigen induced a goodprotection in the immunized animals which was,characterized by survival all immunized animals and nobacterial isolates and pathological changes in the internal organs after infection with P.aeruginosa ascompared with nonimmunized infected animals,which died after infection, with severe bacterial isolatesand sever acute suppurative reaction in their internal organs